Pengaruh Leader Member Exchange dan Perceived Organizational Support Studi Kasus : PT Astra - Siahaan, Lutfiah Hafizah (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2023)
Organizational support on organizational citizenship behavior through organizational commitment at PT Astra. Path analysis research design is used as an analytical tool to determine how the influence between independent and dependent variables is mediated by mediating variables. This study uses associative research with a quantitative approach. The population and samples used in this study were all 125 employees of PT Astra. The results of this research indicate that the variables of leader member exchange and perceived organizational support have a significant effect on organizational citizenship behavior and the variable organizational commitment significantly mediates the relationship between the variables of leader member exchange and perceived organizational support on organizational citizenship behavior.